Gastronomic habits of Serbs and Germans in Indjija prior to the beginning of The World War II - Drča Goran (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Encounter of many nations in the territory of the Srem District in the early and mid-18th century, besides its political and economic aspect, is also interesting to observe from the point of gastronomic diversity. By reviewing the relevant papers written by Serbian and German authors, special contributions that significantly influenced the culture of nutrition were observed during the 19th century. Presence of Germans, Hungarians, Slovaks and other peoples contributed to the formation of habits in the nutrition of Serbs and left a gastronomic mark on this area. Great attention in the paper is dedicated to the presentation of traditional way of preparing food and beverages and the influence of German immigrants on food treatment. Aside from recipes for preparing meals, the paper also covers kitchen utensils and dishes used by housewives, as well as the way houses were built prior to the beginning of the Second World War. The financial situation of households had a great effect on the choice and quality of prepared food. A difficult period for the people affected by wars and complex living conditions certainly contributed to the poor selection of food. However, this did not prevent housewives to show their resourcefulness and make delicious dishes with few available ingredients.